Determination of spectral variations by means of component cells useful for CPV rating and design. (19th November 2015) - Núñez, Rubén; Domínguez, César; Askins, Stephen; Victoria, Marta; Herrero, Rebeca; Antón, Ignacio; Sala, Gabriel
Abstract: A methodology is presented to determine both the short‐term and the long‐term influence of the spectral variations on the performance of multi‐junction (MJ) solar cells and concentrator photovoltaic (CPV) modules. Component cells with the same optical behavior as MJ solar cells are used to characterize the spectrum. A set of parameters, namely spectral matching ratios (SMRs), is used to characterize spectrally a particular direct normal irradiance (DNI) by comparison to the reference spectrum (AM1.5D‐ASTM‐G173‐03). Furthermore, the spectrally corrected DNI for a given MJ solar cell technology is defined providing a way to estimate the losses associated to the spectral variations. The last section analyzes how the spectrum evolves throughout a year in a given place and the set of SMRs representative for that location are calculated. This information can be used to maximize the energy harvested by the MJ solar cell throughout the year. As an example, three years of data recorded in Madrid shows that losses lower than 5% are expected because of current mismatch for state‐of‐the‐art MJ solar cells. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Spectral variation of solar irradiance is analyzed by means of component cells, being useful for multi junction (MJ) and concentrator photovoltaics (CPV) characterization. Filtering using this procedure allows to select very similar spectra to the standard solar spectrum especially convenient to estimate the power rating of CPV systems at standard conditions. When enough spectral data is available, a location can be also characterized, and a MJ design can be optimized to the local spectral conditions.